Coronavirus disease 2019 (COVID-19) polymerase chain reaction (PCR) screening of asymptomatic healthcare workers in a low-prevalence setting: A single-center UK cohort study - Tariq Azamgarhi; Laura Maynard-Smith; Hannah Bysouth; Simon Warren (Cambridge University Press, 2022)
In this cohort study of UK healthcare workers, we evaluated the use of fortnightly polymerase chain reaction (PCR) screening to facilitate the safe resumption of elective surgery in a low-prevalence setting. We found that adherence to serial testing was poor, and the resource required to identify 1 asymptomatic case was substantial.